Comparative Gene Expression Analysis Among Vocal Learners (Bengalese Finch and Budgerigar) and Non-Learners (Quail and Ring Dove) Reveals Variable Cadherin Expressions in the Vocal System - Matsunaga, Eiji; Okanoya, Kazuo (Frontiers in Neuroanatomy, 2011)
Birds use various vocalizations to communicate with one another, and some are acquired through learning. So far, three families of birds (songbirds, parrots, and hummingbirds) have been identified as having vocal learning ability. Previously, we found that cadherins, a large family of cell-adhesion molecules, show vocal control-area-related expression in a songbird, the Bengalese finch. To investigate the molecular basis of evolution in avian species, we conducted comparative analysis of cadherin expressions in the vocal and other neural systems among vocal learners (Bengalese finch and budgerigar) and a non-learner (quail and ring dove). The gene expression analysis revealed that cadherin expressions were more variable in vocal and auditory areas compared to vocally unrelated areas such as the visual areas among these species. Thus, it appears that such diverse cadherin expressions might have been related to generating species diversity in vocal behavior during the evolution of avian vocal learning.